1995
DOI: 10.1063/1.469523
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation study of the interaction of excited neon atoms with BF3: Infrared spectra of BF2, BF+2, BF+3, and BF−3

Abstract: When a Ne:BF3 sample is codeposited at approximately 5 K with a beam of neon atoms that have been excited in a microwave discharge, the infrared spectrum of the resulting solid deposit shows prominent absorptions of BF2. All three vibrational fundamentals and the ν1+ν3 combination band of BF2 isolated in solid neon are identified, and a normal coordinate analysis is conducted. In addition, infrared absorptions of the BF+3, BF+2, and BF−3 molecular ions are assigned, and the processes which occur when the solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…Jacox and Thompson [8] observed for 11 BF 3 + vibrational frequencies of 509.6 cm À1 (out-ofplane) and 1790.8 cm À1 (BF 3 stretch), and noted that the unusually high frequency for the BF 3 + stretching fundamental is consistent with a strong PJT interaction of the 1 2 A 2 0 ground state with 2 E 0 excited states. An absorption at 1661.6 cm À1 , initially assigned to 11 BF 3 + [9], was later reassigned to BF 2 OH + . However, so far there is no direct experimental confirmation of a C 2v state.…”
Section: Introductionmentioning
confidence: 99%
“…Jacox and Thompson [8] observed for 11 BF 3 + vibrational frequencies of 509.6 cm À1 (out-ofplane) and 1790.8 cm À1 (BF 3 stretch), and noted that the unusually high frequency for the BF 3 + stretching fundamental is consistent with a strong PJT interaction of the 1 2 A 2 0 ground state with 2 E 0 excited states. An absorption at 1661.6 cm À1 , initially assigned to 11 BF 3 + [9], was later reassigned to BF 2 OH + . However, so far there is no direct experimental confirmation of a C 2v state.…”
Section: Introductionmentioning
confidence: 99%
“…The observations on BF 2 and BF 2 + and the assignments for these products in the present study are similar to those previously reported. 1 Moderately intense to strong, structured absorptions appeared near 500, 2080, and 2150 cm −1 in all of the discharge experiments. These are readily assigned to F 11 BO and F 10 BO, previously identified in the neon-matrix experiments of Snelson.…”
Section: A Infrared Surveymentioning
confidence: 81%
“…Figure 4, for the 3230 to 3260 cm −1 spectral region, shows two new, weak to moderately intense absorptions which had been above the noise level in only one of the earlier experiments. 1 The photodestruction behavior of several prominent product absorptions falls into two categories:…”
Section: B Results Of Subsequent Irradiationmentioning
confidence: 99%
See 2 more Smart Citations